Parameter selection rules for elements of energy-absorbing structures - OCHELSKI, S.; NIEZGODA, T. (Engineering Transactions, 2009)
The paper presents the results of an experimental program and gives suggestions on the design of an energy-absorbing structure with respect to the kinetic energy of impact. The presented results account for the influence of the following factors on the energy-absorbing capability: matrix and reinforcement type, structure, shape and thickness of elements.